Student Transfer Mobility within Indigenous Programs: Pathways of Access or Appropriation? - Ray, Lana; Toombs, Elaine; Miron, Jeannette (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2023)
Mobility pathways to and from Indigenous programs is one strategy post-secondary education (PSE) institutions employ to support reconciliation, yet data is limited on the status or impact of these pathways. The current study examined program pathways of Indigenous and non-Indigenous learners within Indigenous programming. Fifty-three students were recruited from across PSE institutions in Ontario. Chi squared tests indicated that the majority of students transferring to an Indigenous program were Indigenous, however the study also found that non-Indigenous learners were frequent users of pathways. Results of this study provide cause for consideration about how settler normativity may permeate in pathway development and delivery and recommendations are provided on how PSE can centre Indigenous students in mobility program development.